Dynamical investigation of a supported pipe line section with flowing liquid when intermidiate support is removed - Rimantas Didžgalvis; Antanas Sudintas (Lietuvos Matematikos Rinkinys)
The case, when the oil or gas pipe line is displaced underground, loose the supporting reactions and performs transversal oscillations under the loading, is being analysed. The character of this loading was determined and admitted. Such a mechanical system was described by as the analytical model — the system of differential equation and the solutions were given. Finally, those solutions, could be used for the finding of normal tensions in the walls of the pipes.